2020
DOI: 10.2147/oaem.s241598
|View full text |Cite
|
Sign up to set email alerts
|

<p>Retention of Basic-Life-Support Knowledge and Skills in Second-Year Medical Students</p>

Abstract: Basic life support (BLS) training is crucial in improvement of cardiopulmonary resuscitation (CPR) outcomes. Many studies have demonstrated improvement of skills after BLS training but the skills significantly decrease over time. Our study aimed to evaluate the retention of knowledge and skills after training following 2010 BLS guidelines in second year medical students at Faculty of Medicine, Thammasat University. Materials and Methods: One hundred and forty-nine second-year medical students were enrolled in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In contrast to gender, the results showed that attendance a BLS course previously had signi cant effect on knowledge level. Similar results were reported from Oman, [13] United Kingdom, [18] Pakistan [15] and Thailand [19]. In this study, the numbers of participants who received training about BLS and had knowledge of CPR (massage rate, massage location, massage depth and massage/ventilation rate) were higher than those who did not receive training.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In contrast to gender, the results showed that attendance a BLS course previously had signi cant effect on knowledge level. Similar results were reported from Oman, [13] United Kingdom, [18] Pakistan [15] and Thailand [19]. In this study, the numbers of participants who received training about BLS and had knowledge of CPR (massage rate, massage location, massage depth and massage/ventilation rate) were higher than those who did not receive training.…”
Section: Discussionsupporting
confidence: 87%
“…There was a signi cant difference between the participants from different countries where the mean score in Syria, Jordan and Iraq was 18.3, 24.3 and 18.8 respectively (p < 0.05). The participants were divided into 3 level according to total score; low (0-12), moderate (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) and high (25-37). In total, 18.3%, 72.8% and 8.9% of participants had high, intermediate and low level respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Sufiyah et al reported a decrease in BLS skills after the conventional learning method. They found that a year post-training, only 26% of medical students could complete all BLS steps, and less than 50% of the participants successfully did 3 out of 10 assessment points (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…9 , 20 However, despite initial learning acquisition straight after training, CPR skills normally decay within weeks after initial training. 16 , 54 Although some providers retain CPR skills through recurring exposure to managing cardiac arrests as part of their clinical practice, 55 most paediatric providers go through long periods of clinical practice without performing pCPR due to the low incidence of cardiac arrest in this population. 18 Therefore, it becomes very important to establish retraining intervals to ensure that pCPR skills are maintained for longer.…”
Section: Discussionmentioning
confidence: 99%